Prevalence and factors associated with Tungiasis among school age children in Sub Saharan Africa: A systematic review and meta-analysis. - Gete Berihun; Belay Desye; Leykun Berhanu; Chala Daba; Zebader Walle; Abebe Kassa Geto (PLoS ONE)
Introduction Tungiasis is an overlooked tropical disease resulting from the penetration of the skin by sand fleas. It leads to significant suffering and can be fatal, particularly affecting school age children and elders, primarily above 60 years old, in rural and urban slums across Sub-Saharan Africa. Despite its great public health consequences, the condition remains largely under reported by the scientific communities mainly in Sub Saharan African countries. Objective To assess the prevalence of Tungiasis and associated factors among school-age children in Sub-Saharan Africa. Methods and materials This systematic review and meta-analysis was done based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA 2020). Literatures were searched from a variety of databases, including PubMed, Science-Direct, Google Scholar, Hinari, and Google. The eligible studies data were extracted using Microsoft Excel and exported to statistical software, STATA version 14 for further analysis. A random-effect model was considered to estimate the prevalence of Tungiasis. The Egger test and funnel plot were used to evaluate publication bias, whereas I2 statistic was used to measure heterogeneity. The finding of this SRMA was done using 23 selected studies with 9781 study participants. Results This review revealed that the pooled prevalence of Tungiasis was 37.86%% (95% CI: 30.95-44.77; I2 = 98.3%, P < 0.000). In terms of risk factors of Tungiasis, school children who lived with domestic animals (cat or dog) in their home were 2.73 times more likely to affected by Tungiasis compared to those without these pets in their home (OR: 2.73, 95% CI: 1.53-3.94). Additionally, school age children who did not wear shoes at all and wear occasionally were 11.26 (AOR: 11.26, 95% CI: 4.04, 18.49) and 7.61 (OR: 7.61, 95% CI: 3.39, 11.83) more likely to affected by Tungiasis compared to those who were regularly. Finally, school-age children who lived in mud-plastered walls were 4.97 times more likely to be affected by Tungiasis compared to those who lived in cemented wall homes (OR: 4.97, 95% CI: 2.61, 4.61). Conclusion Generally, this systematic review and meta-analysis disclosed that a third of school age children were affected by Tungiasis. Additionally, housing conditions, shoe-wearing practices, and the condition of living with domestic animals were factors significantly associated with Tungiasis. Hence, concerned governmental and non-governmental organizations should work to enhance behavioral modification towards prevention and control of Tungiasis. One-third of the school-aged children were affected by Tungiasis. Contributing factors included inadequate housing conditions, footwear habits, and the presence of domestic animals. Therefore, relevant governmental and non-governmental organizations should promote behavioral changes to prevent and control Tungiasis.